(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Shown in this paper are methods on how to find the third dimension of a single image or from the two views of the image taking in a different angle using the method more accurate and faster to get to the third dimension in the following cases: One image of the same scene. Two views of the same scene from two different perspectives. Pictures of parts of the same scene. Set of pictures for different views of the work of the subject Panorama. This method is known Image Warping, which falls below a set of transfers such as (Affine - Bilinear - Projective - Mosaic – Similarity transformation) was compared to the work of transfers between the previous and this will be applied to more pictures. The idea is based on building code software is built on the programming language Visual C + + with the library for drawing an OpenGL program Matlab, which way can build a model of the following conversions, which fall under the so-called image warping of the conversion linear Bilinear Mapping and conversion Affine Mapping and conversion imagery Projective Mapping . shown in this paper are methods on how to correct camera exposure changes and how to blend the stitching line between the images. We will show panorama photos generated from both still image.